Gangguan Mental (Mental Disorders) - Kevin Vitoasmara; Fadillah Vio Hidayah; Nofita Ika Purnamasari; Riska Yuna Aprillia; Liss Dyah Dewi A (Student Research Journal, 2024)
Mental disorders are health conditions that affect a person's thoughts, emotions and behavior, often having a significant impact on the sufferer's daily functioning and quality of life. This research aims to examine various types of mental disorders, causal factors, and effective treatment methods. Through the literature review method, data was collected from various relevant scientific sources. Analysis of the literature shows that mental disorders affect approximately 25% of the world's population at some point in their lives, with depression and anxiety disorders being the most common types. The cause of mental disorders is a combination of genetic, biological, psychological and environmental factors. Treatment of mental disorders involves psychological therapy, medication and social support. Cognitive behavioral therapy (CBT) and interpersonal therapy have proven effective in managing the symptoms of mental disorders, while medications such as antidepressants and antipsychotics are often used to control these conditions. Support from family and friends also plays an important role in the recovery process. The conclusions of this research emphasize the importance of a holistic approach in treating mental disorders and the need for public education to reduce stigma. Increased access to quality mental health services and further research are needed to develop more effective treatment methods.